2008
DOI: 10.1038/ng.118
|View full text |Cite
|
Sign up to set email alerts
|

Rare independent mutations in renal salt handling genes contribute to blood pressure variation

Abstract: The effects of alleles in many genes are believed to contribute to common complex diseases such as hypertension. Whether risk alleles comprise a small number of common variants or many rare independent mutations at trait loci is largely unknown. We screened members of the Framingham Heart Study (FHS) for variation in three genes -SLC12A3 (NCCT), SLC12A1 (NKCC2) and KCNJ1 (ROMK)-causing rare recessive diseases featuring large reductions in blood pressure. Using comparative genomics, genetics, and biochemistry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
590
2
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 745 publications
(628 citation statements)
references
References 46 publications
21
590
2
15
Order By: Relevance
“…Bartter's syndrome type II patients (KCNJ1 homozygotes), who lack ROMK expression, have a phenotype characterized by renal salt wasting, hypotension, and mild hypokalemia. 10 Similar observations have also been reported from studies with the ROMK knock out mice. 11,12 In addition, KCNJ1 heterozygote carriers from the Framingham heart study exhibit reduced blood pressure and a reduced risk of hypertension at age 60, when compared with matched controls.…”
supporting
confidence: 80%
“…Bartter's syndrome type II patients (KCNJ1 homozygotes), who lack ROMK expression, have a phenotype characterized by renal salt wasting, hypotension, and mild hypokalemia. 10 Similar observations have also been reported from studies with the ROMK knock out mice. 11,12 In addition, KCNJ1 heterozygote carriers from the Framingham heart study exhibit reduced blood pressure and a reduced risk of hypertension at age 60, when compared with matched controls.…”
supporting
confidence: 80%
“…7,8 Bartter's syndrome type II patients (KCNJ1 homozygotes) lack functional ROMK expression and have a phenotype characterized by renal salt wasting, hypotension, and mild hypokalemia. 9 A similar phenotype has been reported from studies with the ROMK knockout mice. 9,10 In addition, KCNJ1 heterozygote carriers from the Framingham Heart Study exhibited reduced blood pressure and a reduced risk of hypertension at age 60 when compared with matched controls.…”
supporting
confidence: 72%
“…Another hypothesis is that rarer variants in genes implicated in Mendelian forms of stroke may have larger effects. It has already been shown that carriers of genetic variants in genes implicated in Mendelian forms of hyper-or hypotension, are associated with huge variation in BP 40,41 as compared with common SNPs. 21 In the same manner, rare mutations implicated in Mendelian forms of stroke, as well as maternally inherited mitrochondrial mutations, could contribute more than common SNPs to the occurrence of cerebrovascular events.…”
Section: Discussionmentioning
confidence: 99%